Temocillin dosage adjustment in a preterm infant with severe renal disease: a case report. (20th August 2020) - Dumangin, Guillaume; Brenkman, Matthieu; Pape, Elise; Kolodziej, Allan; Gambier, Nicolas; Vrillon, Isabelle; Charmillon, Alexandre; Scala-Bertola, Julien
Abstract: Background: Temocillin is a carboxypenicillin antibiotic indicated in complicated urinary tract infections due to susceptible ESBL-producing Enterobacteriaceae. While temocillin therapeutic schemes for adult patients with normal or impaired renal function are evidence based, little is known in paediatric populations. Objectives: We report herein the management of temocillin treatment in a preterm infant with end-stage renal disease. Patients and methods: The patient was a 7-month-old preterm infant born at 35 weeks gestation and treated by temocillin for 10 days for a bacteraemic urinary tract infection due to a susceptible ESBL-producing Enterobacter cloacae complex strain. Temocillin was administered by continuous infusion using a loading dose of 25 mg followed by a maintenance dose of 70 mg daily. Determination of MIC and temocillin plasma and urinary concentration was performed. Results: Clinical improvement was observed 24 h after the initiation of temocillin treatment. Temocillin concentrations ranged between 21.6 and 35.5 mg/L in urine between the first and the sixth day of treatment and between 47.0 and 61.8 mg/L in plasma after 6 and 10 days of treatment, respectively. Temocillin concentrations were found to be above the determined MIC of 6 mg/L. From the measured concentrations, we can postulate that 100% fT >MIC was achieved in urine and at least equal to 40% in plasma. Conclusions: Temocillin dosing adjustment performed in the present reported case allowed safe and effective treatment. The strategy described herein could be used as a basis for further clinical studies relative to temocillin use in a paediatric population with renal impairment.